Financial performance of Indonesia’s consumer goods companies before and during the Covid-19 Pandemic - Fauziya, Ahada Nur; Jamilah, Iki Khayatul; Novitasari, Budi Tiara; Riantika, Reny Lia (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2023)
This research was conducted due to the significant trend of declining and unstable performance of stock trading in the consumer goods sector during the Covid-19 pandemic. The purpose of this study is to compare the effects of ROA, ROE, NPM, and DER on stock price before and during the Covid-19 pandemic. The secondary data were used and collected through document study. Non-probability sampling was conducted using purposive sampling technique. This research employs a quantitative method and the data were analyzed by smartPLS 3.2.9 program. The results of the study show that ROA has a positive and significant influence on stock price both before and during the Covid-19 pandemic. In addition, ROE and NPM has positive and significant effects on stock price before the Covid-19 pandemic. However, ROE and NPM do not have significant effects on stock price during the Covid-19 pandemic. Similarly, DER does not show a significant effect on stock price both before and during the Covid-19 pandemic.